Physical and social challenges of youth during lockdown in Mizoram: a COVID-19 lockdown study - Lianhmingthangi, Catherine; Harikrishnan, U.; Sailo, Grace Lalhlupuii (International Journal Of Community Medicine And Public Health, 2020)
Background: Young people experience the COVID-19 pandemic differently and their new found ‘leisure’ time can pose several challenges in their physical and social life. This paper incorporates findings from an online survey that was conducted to probe into the physical and social challenges that disrupted the daily life of youth across gender during the lockdown in Mizoram, India. Methods: The study adopted a cross sectional descriptive research design and findings are based on an online survey using Google forms questionnaire administered through different social networking platforms among youth aged between 18-35 years. All respondents are permanent residents of Mizoram, India and the study was carried out during the first and second phases of lockdown across the country. Results: Physical challenges such as abuse, body weakness, laziness and appetite issues were found to be more among female youth while social challenges such as communication and socialization; and inability to maintain social distancing were found to be higher among male youth. Gender is found to have a highly significant relationship with laziness (r=0.069), increased appetite (r=0.086) and decreased appetite (r=0.122) and negative significant relationship with increased substance use (r=-0.183). Conclusions: The study found numerous challenges of youth in Mizoram during lockdown. These crisis calls for intervention of various researchers, policy makers and those working in the field of youth health and development.